Analysis of the implementation of an AIDS mortality committee through municipal health indicators - Mocellin, Lucas Pitrez da Silva (2023)
Background and objective: the acquired immunodeficiency syndrome (AIDS) has high rates of detection and death in the state of Rio Grande do Sul. In order to better understand such deaths, in December 2017, the Uruguaiana Municipal Department of Health implemented the AIDS Mortality Committee (CMaids). This study aimed to analyze the impact of an CMaids implementation in Uruguaiana through municipal health indicators. Methods: an ecological time-series study that used secondary data from the official platforms of the Ministry of Health from 2008 to 2020. Results: a reduction in the indicators number of deaths (from 28 in 2008 to 9 in 2020), mortality rate (from 22.0 in 2008 to 7.1 deaths/100,000 inhabitants in 2020), and fatality rate (from 46.74 in 2008 to 9.61 deaths/1,000 inhabitants in 2020). Moreover, trend lines were verified between 2017-2020 through the logarithmic regression model with join points. A relevant Annual Percent Change in mortality and fatality indicators was verified, with a reduction of 59.1% and 73.4%, respectively, in 2020, when comparing the observed and expected values. Conclusion: the findings enable us to conjecture that CMaids contributed to health indicator improvement, evidencing this as a relevant strategy to handle HIV/AIDS endemic at the local level.